ASP.NET 3.5 Website programming : problem-design-solution - Love, Chris (Wrox problem--design--solution., 2010)
Uses the popular Problem;Design;Solution format to help readers, especially those who know how to code specific ASP.NET features, learn to ""put it all together"" into a complete Web applicationEmphasizes n-tier ASP.NET Web application architectural design, something intermediate and advanced ASP.NET developers need and can't find anywhere elseCurrent edition is the most popular and discussed book in the p2p.wrox.com reader discussion forumsCovers registration and membership system, user-selectable themes, content management systems, polls, mailing lists, forums, e-commerce.